Pengaruh Konten Instagram @Baweantourism terhadap Tingkat Wawasan Followers - Nuzulur Rahman; Agus Ainul Yaqin M.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
The rise of social media has transformed how people access information, including tourism insights. This study analyzes the influence of Instagram content on @baweantourism toward followers' knowledge levels. Using a descriptive quantitative approach, data were collected through questionnaires and analyzed statistically. The study is grounded in mass communication and media effects theory. Findings reveal a positive and significant impact of Instagram content on user awareness, indicated by t-count (19.070) > t-table (1.982) and a significance level of 0.000 < 0.05. The study concludes that social media serves as an effective tool for promotion and education in raising public knowledge about local destinations such as Bawean.